New phytoseiid mites (Acari: Phytoseiidae) from tropical Africa - de Moraes, G。 J.; Oliveira, A. R.; Zannou, I. D. (Zootaxa, 2001)
Five new mite species of the family Phytoseiidae (Acari: Mesostigmata) are described from Central Africa: Typhlodromalus breviscutus n. sp., Typhlodromips occidentafricanus n. sp., Typhlodromips extrasetus n. sp., Australiseiulus laterisetus n. sp. and Typhlodromus (Anthoseius) cephalochaitosus n. sp.